A centralidade da família na política da assistência social - Lima, Francisca Benigno (Universidade Federal do Tocantins, 2022)
This Course Completion work aims to analyze the Social Assistance Policy and the centrality of the family, based on official documents. As an object of study the centrality of the family in the Social Assistance Policy, a bibliographic review of authors was used as methodological techniques and documental research of the main laws of the Social Assistance Policy: the National Social Assistance Policy - PNAS/2004, the structuring and the standardization of the Unified Social Assistance System - SUAS and the Organic Law of Social Assistance - LOAS. Thus, the research was qualitative, guided by the Historical and Dialectic Method, considering that the social assistance policy and its relationship with the family must be analyzed from the perspective of totality. The research presented as main ideas, the approach to the family, its history, forms of organization mainly from the class division and the emergence of private property, to get into how the capitalist mode of production implies on families to understand the multiple elements such as (patriarchy, gender, sexual division of labor, family responsibilities, social roles, subsistence, social relations etc.) involving capitalist society and the family, the second point was to address the relationship between social protection and families, especially within the Policy of Social Assistance to understand the responsibilities demanded of families to offer social protection to their family members. The study showed, according to the analysis of the Social Assistance policy documents, that despite the recognition of the social assistance policy as a right of the subjects, there is a centrality on the family and as this centrality exists, in the provision of services, programs, benefits and projects, since the requirement of access criteria is more exclusive than inclusive, there is also the responsibility of the family for the promotion of well-being, that is, a familist practice coined in a socio-historical-cultural process. But above all, we emphasize the importance of having a Social Assistance Policy as something to be offered to families, as well as the search for ways that can broaden the debate and spaces that always bet on the construction of a Social Assistance Policy based on Social protection for families, always seeking to remove responsibility and increasingly expand their rights.